2011
DOI: 10.1111/j.1365-246x.2011.05132.x
|View full text |Cite
|
Sign up to set email alerts
|

Multistep modelling of teleseismic receiver functions combined with constraints from seismic tomography: crustal structure beneath southeast China

Abstract: S U M M A R YWith a growing number of modern broad-band seismographic stations in Asia, the conditions have improved to allow higher resolution structural studies on regional scales. Here, we perform a receiver-based study of the lithosphere of southeast China using waveform records of excellent quality from 14 Chinese National Digital Seismic Network and four Global Seismic Network stations. Calculating the theoretical receiver functions (RFs) that match the observed RFs from teleseismic waveforms is an estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 52 publications
(75 reference statements)
1
62
0
Order By: Relevance
“…Depth ( Barazangi and Brown 1986a,b Barton and White 1997Becker et al 2012Blundell and Raynaud 1986Breivik et al 2003Broucher 1995Bullock and Minshull 2005Chian et al 1995Christeson et al 2008Clegg and England 2003Clowes et al 1999Clowes et al 1987 Pavlenkova et al 2009Prajapati et al 2011Qiu et al 2001Ritzmann et al 2002Roberts et al 1988Rubio et al 2000Sage et al 2000Stankiewicz et al 2008Suckro et al 2012Thréhu et al 1994Tkalcic et al 2011Toomey et al 2007Todd et al 1988Torne et al 2003Vuan et al 2005Wang et al 2004a,b Watremez et al 2011White and McKenzie 1989White and Smith 2009White et al 1987a,b Worthington et al 2012…”
Section: Principal Crustal Typesmentioning
confidence: 97%
“…Depth ( Barazangi and Brown 1986a,b Barton and White 1997Becker et al 2012Blundell and Raynaud 1986Breivik et al 2003Broucher 1995Bullock and Minshull 2005Chian et al 1995Christeson et al 2008Clegg and England 2003Clowes et al 1999Clowes et al 1987 Pavlenkova et al 2009Prajapati et al 2011Qiu et al 2001Ritzmann et al 2002Roberts et al 1988Rubio et al 2000Sage et al 2000Stankiewicz et al 2008Suckro et al 2012Thréhu et al 1994Tkalcic et al 2011Toomey et al 2007Todd et al 1988Torne et al 2003Vuan et al 2005Wang et al 2004a,b Watremez et al 2011White and McKenzie 1989White and Smith 2009White et al 1987a,b Worthington et al 2012…”
Section: Principal Crustal Typesmentioning
confidence: 97%
“…b Seismograms from a are band-pass filtered with cutoff frequencies of 2 and 5 Hz. c The selected set of coherent waveforms after employing the cross-correlation matrix method (Tkalčić et al, 2011) is shown by cyan lines and PcP. On the right side, G represents the geometrical spreading factor; f 0 (=1 Hz) and f are reference and observed frequencies, respectively; T PK and T KP are the transmission coefficients at the CMB; and R PP and R KK denote reflection coefficients at the CMB and ICB, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We then selected subsets of coherent waveforms by using the cross-correlation matrix method (Tkalčić et al 2011), which retained 46-220 records per event. To find coherent PKiKP arrivals in each sub-group, we empirically determined the minimum percentage (τ) of all waveform pairs that should cross-correlate in such a way that the average crosscorrelation coefficient equals or exceeds a threshold β.…”
Section: Methodsmentioning
confidence: 99%
“…Fontaine et al 2013a;Lamarque et al 2015). Before each stack, we examine the coherency of individual RFs using the cross-correlation matrix approach from Tkalčić et al (2011): we compute the cross-correlation coefficients for each pair of RFs. Then individual RFs are selected or rejected using empirical values for the minimum coefficient of cross-correlation χ and the percentage of coherent RFs τ .…”
Section: R F O B S E Rvat I O N Smentioning
confidence: 99%